PEASANTS, CAPITALISM, AND THE WORK OF ERIC R WOLF - Tilzey, Mark. ([S.l.])
1 online resource.
Keywords: Fifty years after the publication of Eric Wolf's celebrated Peasant Wars of the Twentieth Century, and forty years after the publication of his path-breaking Europe and the People Without History, this book offers a much-needed critical assessment and update of Wolf's contribution to the study of the peasantry and its relationship to capitalism, the state, and imperialism. This book provides a comprehensive evaluation of Wolf's premises, methodology, and understanding of the peasantry, and its relationship to the rise of capitalism and the modern state. The authors analyse Wolf's theoretical approach and, by building on his work in Europe and the People Without History especially, argue their own position concerning the dynamics of the peasantry in relation to capitalism, state, class, and imperialism. Further, the text aims to answer the agrarian question more widely, focusing on agrarian society and the political role of the peasantry in contested transitions to capitalism and to modes beyond capitalism. This requires, the authors argue, an analysis of class struggle and of the resources, material and discursive, that different classes can bring to bear on this struggle. Based on well-founded theoretical premises, the book focuses on the contested rise of capitalism in the global North, the development of core-periphery relations in the global political economy, and the place of the peasantry in these dynamics. The book presents case studies of transitions to agrarian capitalism in the British Isles, France, Germany, Japan, and the USA. The book will be of great interest to students and researchers in the areas of peasant studies, rural politics, agrarian studies, development, and political ecology.